Incidencia del cambio climático sobre la distribución espacial de tres de las especies de aves con mayor grado de amenaza en Colombia (2023)
The number of threats faced by different species has been increasing after the accelerated human activity, in terms of the destruction of ecosystems, deforestation, excessive use of natural resources, expansion of the urban and agricultural frontier, among others, which has generated a constant pressure on biodiversity and detriment to the number of species on the planet. In addition, and as part of the consequence of the previous acts, it would be necessary to add the climate change and its effects.